Corpus-based Interpreting Studies as an Offshoot of Corpus-based Translation Studies - Shlesinger, Miriam (Meta, 1998)
AbstractThis article looks at the problems and benefits that may arise from applying a corpus- based methodology to the study of interpreting. It explores two ways in which interpreting could be fruitfully investigated with the aid of corpora. The first is direct and involves the design of new types of parallel and comparable corpora. The second consists of employing existing monolingual corpora to extract material that can be used in experimental research into interpreting.